Perceived parenting styles of juvenile delinquents - مساوي , محمد; كركوش , فتيحة (مجلة دراسات في سيكولوجية الانحراف, 2024)
This study aimed to reveal the methods of perceived parental treatment that are most prevalent among juvenile delinquents, in addition to some socio-demographic characteristics represented in the nature of housing, educational level and monthly income of the parents. The study was carried out on a sample of thirty (30) juvenile delinquents, ages of whom, ranged between 10 to18 years. This was done under the descriptive analytical approach, where the EMBU scale was used for parental treatment, after verifying its validity and reliability. The results of the study concluded that the most prevalent perceived parental treatment methods among juvenile delinquents are of both normal and abnormal styles. There are statistically significant differences with regard to the perceived parental treatment methods of juvenile delinquents due to the following variable: the nature of housing and the parents monthly income. We keep in mind the existence of non-statistically significant differences with regard to the perceived parenting methods of juvenile delinquents due to the educational level of the parents.